Prolonged response to recombinant human erythropoietin treatment in patients with myelodysplastic syndrome at a single referral centre in Brazil - Moura, Anna Thawanny Gadelha (2019)
OBJECTIVES: To evaluate the effects of epoetin (EPO) alfa treatment on overall survival, event-free survival and response duration in patients with myelodysplastic syndrome (MDS) who were treated at a haematological referral centre in northeastern Brazil. METHODS: This was a retrospective cohort study of 36 patients diagnosed with MDS and treated with EPO alfa at 30,000 to 60,000 IU per week. Clinical data were collected from medical records. The events assessed were non-response to treatment and progression to acute myeloid leukaemia (AML). Statistical analyses were performed using GraphPad Prism 7 and SPSS 24 software. RESULTS: The overall survival of patients who received EPO alfa treatment was 51.64%, with a median of 65 months of treatment, and the overall survival of this group was 100% during the first 24 months. We detected a 43.5-month median event-free survival, with a response rate of 80.5%. We observed responses from 25 to 175 months. Patients with transfusion dependence and those with a high-risk stratification, as determined by the International Prognostic Scoring System (IPSS), the Revised International Prognostic Scoring System (IPSS-R), the WHO classification-based Prognostic Scoring System (WPSS) and the WHO 2016, had a lower event-free survival than other patients. CONCLUSIONS: Despite the wide use of EPO alfa in the treatment of anaemia in patients with MDS, the median response duration is approximately only 24 months. Our data provide encouraging results concerning the benefits of using EPO alfa for the improvement of the quality of life, as patients treated with EPO showed higher overall survival, event-free survival rates and longer response durations than have been previously described in the literature.